How an Intranet Provides Opportunities for Learning Organizational Culture - Elisabeth E. Bennett (Adult Education Research Conference, 2007)
This paper discusses a qualitative case study that addressed how an intranet can provide opportunities for learning about an organization’s culture. Four primary findings are discussed with the study concluding that cultural knowledge is conveyed and renewed through intranet in the learning process.